2011
DOI: 10.1097/hjh.0b013e328342ef04
|View full text |Cite|
|
Sign up to set email alerts
|

Blood pressure control by the nifedipine GITS–telmisartan combination in patients at high cardiovascular risk: the TALENT study

Abstract: on behalf of the TALENT investigatorsBackground Guidelines on hypertension regard combinations between two antihypertensive drugs to be the most important treatment strategy. Because of the complementary mechanism of action and the evidence of cardiovascular protective effects they include the combination of a calcium antagonist and an angiotensin receptor antagonist among the priorital ones to employ. AimsTo determine in hypertensive patients at high cardiovascular risk whether combining Nifedipine GITS at lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
27
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 34 publications
3
27
0
1
Order By: Relevance
“…The superior BP reductions of combination therapy were maintained throughout the 8‐week study. The results are also consistent with previous studies of combination therapy consisting of a CCB and an ARB 28, 29, 30, 31. Importantly, a greater and earlier effect on BP control via combination therapy has the potential to provide greater CV benefit, as suggested by meta‐analysis2 and by review of major clinical trials with CCB/RAS blocker therapies 32…”
Section: Discussionsupporting
confidence: 87%
“…The superior BP reductions of combination therapy were maintained throughout the 8‐week study. The results are also consistent with previous studies of combination therapy consisting of a CCB and an ARB 28, 29, 30, 31. Importantly, a greater and earlier effect on BP control via combination therapy has the potential to provide greater CV benefit, as suggested by meta‐analysis2 and by review of major clinical trials with CCB/RAS blocker therapies 32…”
Section: Discussionsupporting
confidence: 87%
“…The most obvious explanation is that, as also shown in our patients by the tertiles data, not only office but also ABP reductions are proportional to baseline BP values, which means that little BP lowering effect can be expected when, as in WCH, the initial ABP is normal or low. However, in other antihypertensive treatment studies, 36,37 ABP has been reduced below the baseline values exhibited by the WCH patients of the present study, and we have thus to consider the possibility that the easy response of office BP to treatment that characterized WCH prevented lower ABP values from being achieved. Furthermore, in our WCH patients, ABP often showed not just no change but an increase, which was consistent in patients with baseline ABP in the lowest tertile.…”
Section: Discussionmentioning
confidence: 61%
“…34 Another novel and clinically relevant contribution of our study is the information on the BP effects at high altitude of a commonly used and guideline-supported combination treatment between an ARB and a slow release calcium antagonist. 16,17 Two previous studies reported that β-blockers have a limited effect in preventing the 24-hour BP increase that occurs at high altitude, 8,28 and their use (particularly of carvedilol) is associated with lower SpO 2 , worse tolerability, and exercise capacity. 8,35 In the healthy participants of HIGHCARE-HIMALAYA, we observed that BP-lowering effect of telmisartan monotherapy was maintained ≤3400 m but not at higher altitudes (5400 m), with no tolerability issues.…”
Section: Discussionmentioning
confidence: 99%
“…17 In the hypertensive participants of the present study, the combined treatment with telmisartan and nifedipine was effective and safe at an altitude (3260 m) similar to the lower altitude reached in HIGHCARE-HIMALAYA, with BP values that remained lower than in placebo-treated subjects, as it occurred at sea level. Moreover, the active treatment group had higher SpO 2 at high altitude (possibly because of the dilatory effect of nifedipine on pulmonary vasculature leading to improved ventilation:perfusion ratio), even if no differences in acute mountain sickness were found between treatment groups.Our study has several elements of strengths including: (1) adequate sample size, (2) controlled double-blind design, and (3) assessment of the BP effect of high altitude and treatment by ambulatory BP monitoring, an approach that is prognostically superior to conventional BP measurements 16 and that better reflects the high altitude-related BP alterations. 17 The study also has some inevitable limitations.…”
mentioning
confidence: 99%
See 1 more Smart Citation